INTERNATIONAL CONGRESS OF AMERICANISTS IN MEXICO CITY - ANONIMO (INTERNATIONAL CONGRESS OF AMERICANISTS, CD. MEXICO, DF, MEX, 1946)
A broadsheet issued by Political and Economic Planning (P E P) reviews the present position of the joint industrial councils and their development from the Whitley Committee in 1916. During 1918-21, National Whitley Councils were established in 80 industr
NATURE
Keywords: INTERNATIONAL CONGRESS OF AMERICANISTS, MEXICO CITY; MULTIDISCIPLINARIA